Design of an Open Electrowetting on Dielectric Device Based on Printed Circuit Board by Using a Parafilm M - Yi, Zichuan; Feng, Haoqiang; Zhou, Xiaofeng; Shui, Lingling (Frontiers in Physics, 2020)
In recent years, the open electrowetting on dielectric (EWOD) device has been widely used in biomedical detection, chemical synthesis analysis, and so on. However, the cost of using ITO glass as surface material is difficult to meet the requirement for large-scale array chip production. So, a low-cost, easy-to-manufacture open EWOD platform is designed in this paper. In hardware platform, an operation platform is prepared by using a printed circuit board (PCB) as a substrate. The electrode shape is designed as zigzag, and its surface is optimized by organic solderability preservatives (OSP). In addition, Parafilm M and silicone oil are used as a dielectric hydrophobic layer to prepare the open platform. In software, the system program is designed by C programming language, including initialization program, serial port communication program, high-voltage output port program, and interrupt program, which can be used to drive droplets. The system can achieve an effective driving voltage of 180–240 V. The moving speed of droplets can reach 15 mm/s when the droplet volume is 1850 μL and the electrode voltage output frequency is 10 Hz.